Septicaemia caused by Myroides spp.: a case report. Issue 5 (23rd September 2015) - Elantamilan, D.; Lyngdoh, Valarie W.; Choudhury, Basabdatta; Khyriem, Annie B.; Rajbongshi, Jyotismita
Abstract : Introduction: Myroides spp. are aerobic, yellow-pigmented, non-fermentative Gram-negative rods considered to be low-grade opportunistic pathogens. However, their intrinsic resistance to commonly used antibiotics necessitates prompt identification and evaluation. Case presentation: Here, we report a case of septicaemia caused by Myroides sp. A 36-year-old pregnant female was admitted to the intensive care unit at week 18 of gestation with a diagnosis of hydatidiform mole with acute renal failure and anaemia. Blood culture under aerobic conditions showed growth of round, smooth, convex, yellow-pigmented colonies on blood agar but which failed to grow on MacConkey agar, and the organism was identified as Myroides sp. Susceptibility testing showed that it was susceptible only to piperacillin+tazobactam and, following treatment, the patient recovered. Conclusion: Myroides spp. has, until now, been regarded as an opportunistic pathogen and a rare cause of serious disease in immunocompromised subjects. However, it may cause serious disease, even in immunocompetent hosts, and its intrinsic resistance warrants appropriate testing and timely intervention.